IMPLEMENTASI MODEL PEMBELAJARAN TEAMS GAME TOURNAMENT PADA PROGRAM KAMPUS MENGAJAR 6 DALAM UPAYA PENINGKATAN KEMAMPUAN NUMERASI KELAS V SD NEGERI KEDUNGWUNGU 03 GROBOGAN - Utami, Wulan; Panca Dewi Purwati (Elementeris : Jurnal Ilmiah Pendidikan Dasar Islam, 2024)
This study's motivation stems from the idea that students' numeracy skills are always in the spotlight so that they require special treatment. This research aimed to describe the application of Teams Game Tournament type Cooperative Learning model Tournament in order to enhance the numeracy abilities of fifth grade at Kedungwungu 03 Grobogan elementary school. The method used in this research is classroom action research method. The subjects of this research were fifth grade students at Kedungwungu 03 Grobogan elementary school, totaling 21 students. The results of this study indicate that the implementation of the Teams Game Tournament type Cooperative model can improve students' numeracy skills which can be seen from the comparison of pretest and posttest scores with an increase of 1.44%, namely from 27.3% to 39.5%. Keywords: Teams Game Tournament, Numeracy, Elementary School.